Decolonizing the Lens of Power: Indigenous Films in North America - Kerstin, Knopf (Rodopi, 2008)
Knopf samples a variety of Native American filmmaking genres, including documentary, short films, and full-length narrative films, providing a detailed synopsis and content analysis of several films. Since its genesis in the early 19005, film has been an effective colonizing tool, impacting Indigenous peoples around the globe.
Issue: 4 Pages: 611-614
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Provincializing Hegemonic Histories of Media and Communication Studies: Toward a Genealogy of Epistemic Resistance in Africa - Willems, Wendy (Communication Theory, 2014)
In the late 1990s and 2000s, a number of calls were made by scholars to “internationalize” or “dewesternize” the field of media and communication studies. I argue that these approaches have indirectly silenced a much longer disciplinary history outside “the West” that has not only produced empirical knowledge but has also actively challenged Western epistemologies. This article seeks to reinscribe the epistemological and historical foundations of media and communication studies in Africa. By framing the research of African media and communication scholars within the changing nature of knowledge production, shifting power relations between African nations, and the evolving role of African universities, I demonstrate how academic knowledge production is frequently driven and constrained by particular dominant social, political, and economic interests.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12043
Keywords: 1-Cinéma; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Queer Times, Black Futures - Kara Keeling (New York University Press, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

De-Westernizing Film Studies - Ba, Saer Maty; Higbee, Will (Routledge, 2012)
De-Westernizing Film Studies aims to consider what form a challenge to the enduring vision of film as a medium - and film studies as a discipline - modelled on ‘Western’ ideologies, theoretical and historical frameworks, critical perspectives as well as institutional and artistic practices, might take today. The book combines a range of scholarly writing with critical reflection from filmmakers, artists & industry professionals, comprising experience and knowledge from a wide range of geographical areas, film cultures and (trans-)national perspectives. In their own ways, the contributors to this volume problematize a binary mode of thinking that continues to promote an idea of ‘the West and the rest’ in relation to questions of production, distribution, reception and representation within an artistic medium (cinema) that, as part of contemporary moving image culture, is more globalized and diversified than at any time in its history. In so doing, De-Westernizing Film Studies complicates and/or re-thinks how local, national and regional film cultures ‘connect’ globally, seeking polycentric, multi-directional, non-essentialized alternatives to Eurocentric theoretical and historical perspectives found in film as both an artistic medium and an academic field of study. The book combines a series of chapters considering a range of responses to the idea of 'de-westernizing' film studies with a series of in-depth interviews with filmmakers, scholars and critics. Contributors: Nathan Abrams, John Akomfrah, Saër Maty Bâ, Mohammed Bakrim, Olivier Barlet, Yifen Beus, Farida Benlyazid, Kuljit Bhamra, William Brown, Campbell, Jonnie Clementi-Smith, Shahab Esfandiary, Coco Fusco, Patti Gaal-Holmes, Edward George, Will Higbee, Katharina Lindner, Daniel Lindvall, Teddy E. Mattera, Sheila Petty, Anna Piva, Deborah Shaw, Rod Stoneman, Kate E. Taylor-Jones
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé